Multicharge β-cyclodextrin supramolecular assembly for ATP capture and drug release. Issue 22 (19th February 2021) - Chen, Changhui; Chen, Yong; Dai, Xianyin; Li, Jingjing; Jia, Shanshan; Wang, Shuaipeng; Liu, Yu
Abstract : A hyaluronidase-responsive polysaccharide supramolecular assembly for targeted drug release and capturing ATP, with enhanced efficacy of anticancer drugs on cancer chemotherapy. Abstract : A hyaluronidase-responsive polysaccharide supramolecular assembly was constructed from an amphiphilic β-cyclodextrin bearing seven hexylimidazolium units (AMCD), adamantyl-grafted hyaluronic acid, and chlorambucil, which showed specific cancer cell targeting and controlled drug release abilities. Interestingly, ternary supramolecular assembly can disassemble in the presence of hyaluronidase, and the released AMCD can assemble with ATP to form a stable 1 : 1 complex, which enhanced the efficacy of chlorambucil on cancer chemotherapy by inhibiting ATP hydrolysis.